2007
DOI: 10.1002/prep.200700041
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Analytical Model for Reactive Particle Ignition in Explosives

Abstract: A simple analytical model is developed to predict ignition of magnesium particles in nitromethane detonation products. The flow field is simplified by considering the detonation products as a perfect gas expanding in a vacuum in a planar geometry. This simplification allows the flow field to be solved analytically. A single particle is then introduced in this flow field. Its trajectory and heating history are computed. It is found that most of the particle heating occurs in the Taylor wave and in the quiescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…These mechanisms would allow the reaction initiation temperature to be significantly below the melting point of the oxide. These were the conclusions by Tanguay et al [18] and Frost et al [19,20] who further assumed the initiation temperature to be the melting point of aluminum irrespective of its size.…”
Section: Particle Surface Temperaturesupporting
confidence: 69%
“…These mechanisms would allow the reaction initiation temperature to be significantly below the melting point of the oxide. These were the conclusions by Tanguay et al [18] and Frost et al [19,20] who further assumed the initiation temperature to be the melting point of aluminum irrespective of its size.…”
Section: Particle Surface Temperaturesupporting
confidence: 69%
“…The particles are further accelerated from the reflected expansion as the shock wave arrives at the free-surface of the particles. When the detonation front first arrives at a particle, momentum is imparted by pressure and viscous forces and the temperature is raised by the high-temperature combustion products [4]. It has also been observed that certain size particles may have enough momentum to catch and penetrate the decelerating contact surface (fireball), see Figure 2.7.…”
Section: Explosive Dispersalmentioning
confidence: 99%
“…The metallic powders in an EBX do not react quickly enough to contribute to the detonation front [4], but they are able to contribute to the blast wave energy. This is possible because they react within the products of the condensed explosive.…”
Section: Reaction Time Scalementioning
confidence: 99%
See 2 more Smart Citations